Selective methane oxidation on MoO3/SiO2 - Wang, Hongru (2013)
Heterogeneous oxidation of methane over various metal catalysts is of interest due to the application of green energy production, e.g. CH2O and CH3OH. Although significant progress has been made these years, the conversion and selectivity are still limited primarily by rapid oxidation of CH2O.